Metastatic pelvic lymph node ratio may predict the prognosis of the IIIC1 cervical cancer patient - Tomasz Leks; Agnieszka Koper; Sebastian Szubert; Łukasz Witek; Jakub Szpiech; Joanna Terlikiewicz; Bożena J. Cybulska-Stopa; Magdalena Dutsch-Wicherek; Krzysztof Koper; Łukasz Wicherek (Nowotwory)
INTRODUCTION: Nodal status is a major factor influencing the survival rates of cervical cancer patients. According tothe 2018 International Federation of Gynecology and Obstetrics (FIGO) classification system, the presence of lymphnode metastases is a criterion for stage IIIC cervical cancer. In contrast to merely indicating the presence or absenceof lymph node metastases, calculating the lymph node ratio LNR [number of positive lymph nodes (LNs)/number of harvestedLNs] can provide additional clinical information about nodal status. In a group of node-positive patients whohad early-stage cervical cancer followed by surgical treatment, high LNR was associated with poor patient survival. MATERIAL AND METHODS: In the present retrospective study, 5-year and 10-year overall survival rates for 310 patientsdiagnosed with stage IB–IIA cervical cancer were analyzed based on the 2009 FIGO classification system. Of thesepatients, 72 had lymph node metastases. We evaluated the number of metastatic LN and calculated the LNR. We thenassessed the 5-year and 10-year overall survival (OS) in relation to the LNR. RESULTS: The multivariant survival analysis of a group of 72 patients with pelvic lymph node metastases revealed that0.25 was the optimal LNR cutoff value for differentiating between short-term and long-term survivors. CONCLUSIONS: Lymph node ratio may be used to stratify a high-risk population of patients with cervical cancer and maybe crucial for identifying those patients who might benefit from adjuvant therapy.